Assessment of Management of Waste Collection and Disposal in Bauchi Metropolis Bauchi State, Nigeria - Ahmed, Fahad; Muhammad, Salisu Umar; Umar, Ahmed Faruk (International Journal of Science Education and Science, 2025)
Waste management is the process of collecting, transporting, processing or disposing, managing and monitoring of waste materials. Poor waste management has been a major problem to human health and existence, affecting both rural and urban areas. The study used survey research design adopted a quantitative method because of its appropriateness to the topic under investigation. In most low to medium income developing nations like Nigeria, almost 100 percent of generated waste goes to landfills, while wastes are deposited in open dumps in developing nations; these have become obsolete in the developed countries. The educated respondents are significantly more likely than the less educated to dispose of waste through composting (p < 0.05) and incineration (p < 0.025). However, the less educated are more likely to dispose of refuse by open dumping (p < 0.05), burning and burying (p < 0.05), and also more likely to hand carry refuse (p < 0.025) and transport refuse by wheel barrow (p < 0.025) than the more educated would do. Majority of the respondents (75.90%) have a centralized place for dumping solid waste and the commonest means of transports of waste was by wheel barrow (70.20%). The repeated measure regression was used to allow comparisons among the variables under each condition. For finding depicts many factors like current methods, source of information, types of waste generated and waste management practices of waste collection and disposal. The finding shows that if public and private sector provides necessary consideration and utilization of practice of west collection and disposal, and encouragement of awareness on the uses of recycling method and practice to the Bauchi Metropolis. Multiple regressions were conducted to test the above-mentioned assessment.